Penerapan Wireless Sensor Network (Wsn) Dengan Topologi Tree Pada Pemantauan Tanah Longsor - Lesmana, Wahyu Indra; Harianto, Harianto; Wibowo, Madha Christian (JAVA Journal of Electrical and Electronics Engineering, 2015)
Currently wireless technology has grown rapidly. Wireless technology is wireless communication technology, and currently has a lot of growing up and one of the developments is the wireless sensor networks (WSN). WSN is a combination of wireless modules, micro module and the sensor module, the workings of WSN is the sensor response value to the microcontroller module and the response values are transmitted via wireless communication. Based on how the WSN can be used for various purposes with one of them for monitoring natural disasters. WSN is designed for monitoring natural disasters landslides. In general WSN systems have problems such as limited distance. In this system, the authors apply topology tree and spanningtreeprotocol (STP). Tree topology is a collection of star topology are connected into the bus topology as spine or backbone lines, while STP is a network communications protocol that has automatic backup paths if the main line is not active. By implementing this system, the maximum distance of the receiving and sending data of node to node is 100 meters, while by applying tree topology and spanningtreeprotocol within a maximum range on the whole system is 141 meters. With these results it can be concluded that the overall system using a maximum distance of wider scope.